High-brightness high-wear-resistance high-strength vehicle-mounted light guide plate
Patent Information
- Application Number
- CN202611277318.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的是提供一种高亮高耐磨高强度车载导光板,解决了现有车载导光板表面微结构会磨损,且注塑成型时会产生困气导致微结构复型保真度和光学性能下降的问题
[0032] 1. This invention uses fluorinated end-capped poly(carbonate-siloxane) block copolymer as a modifying component of the matrix material. During the injection molding stage, based on the low surface energy characteristics of the fluorinated and siloxane segments, a release slip layer is formed on the surface of the light guide plate. The release slip layer reduces the adhesion between the light guide plate and the mold cavity, reduces the frictional resistance during the demolding process, thereby reducing the shear stress damage to the surface microstructure during demolding. The surface layer after molding also reduces the friction coefficient of the final product and improves the scratch resistance and wear resistance of the light guide plate.
Smart Images

Figure CN122883305A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of automotive display technology, and in particular to a high-brightness, high-wear-resistant, and high-strength automotive light guide plate. Background Technology
[0002] Light guide plates are common optical components in automotive displays and interior ambient lighting systems. Their main function is to uniformly guide light from the side to the light-emitting surface through internal total internal reflection. Currently, automotive light guide plates are mostly made of polycarbonate material through injection molding, and rely on the design of micro-dot structures on the surface to disrupt the total internal reflection conditions, thereby controlling the overall light output effect.
[0003] In actual vehicle use, the light guide plate needs to withstand the vibration generated by vehicle operation for a long time and face daily wiping and cleaning. Conventional polycarbonate materials have a high surface friction coefficient. The micro-nano optical structures exposed on the surface will be scratched and worn in physical contact. Once the mechanical morphology of the surface structure is damaged, the originally designed light path transmission will be deviated, causing the light guide plate to have local light leakage, brightness reduction and overall light output uniformity reduction.
[0004] To improve the optical performance of light guide plates, existing dot microstructure designs tend to be miniaturized and complex. This also brings process obstacles to the injection molding process. During the injection stage, the polymer melt faces significant flow resistance when filling the tiny blind cavities on the mold surface. Gases remaining inside the cavity and at the edges of the structure are difficult to expel in time. This localized gas trapping phenomenon hinders the full filling of the melt, resulting in insufficient glue or material at the top or edges of the microstructure. In addition, after the polycarbonate melt cools and solidifies, it has a high adhesion force to the mold cavity surface. During the mold opening and ejection step, the micron-sized dot structure is subjected to significant frictional resistance, resulting in shear stress damage or root tensile deformation. Poor mold filling and demolding damage during the molding process are superimposed, leading to low fidelity of microstructure replication, which ultimately affects the overall optical quality of the light guide plate. Summary of the Invention
[0005] The purpose of this invention is to provide a high-brightness, high-wear-resistant, and high-strength automotive light guide plate, which solves the problems of wear on the surface microstructure of existing automotive light guide plates and the reduction in microstructure fidelity and optical performance caused by trapped air during injection molding.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides a high-brightness, high-wear-resistant, and high-strength automotive light guide plate, which is made of an optical molding composition comprising the following components in parts by weight:
[0008] 75 to 85 parts of bisphenol A type polycarbonate;
[0009] 14.5 to 24.5 parts of a fluorinated end-capped polycarbonate-siloxane block copolymer that is enriched on the surface during injection molding to reduce surface free energy and form a release slip layer;
[0010] 0.2 to 0.4 parts of tris(2,4-di-tert-butylphenyl) phosphite;
[0011] 0.1 to 0.3 parts of 2,2H-benzotriazol-2-yl-4,6-bis(1-methyl-1-phenylethylphenol);
[0012] The light guide plate has an elliptical dot array formed by a composite transfer distributed on the light incident side distal surface. The edges of the elliptical dots have amorphous or microcrystalline annular remelted protrusion microstructures to deflect and converge the diverging outgoing light beam toward the normal direction.
[0013] Due to the use of fluorine-terminated polycarbonate-siloxane block copolymers and composite microstructure design, the specific working process is as follows:
[0014] During injection molding, the fluorinated alkyl segments and siloxane segments in the fluorinated end-capped polycarbonate-siloxane block copolymer have low surface energy. These low surface energy segments tend to migrate and accumulate on the surface of the light guide plate during the melt filling and cooling solidification stages. The fluorinated and siloxane groups accumulated on the surface form a release slip layer on the surface of the light guide plate, reducing the surface free energy of the light guide plate and the adhesion force with the mold cavity surface, reducing the frictional resistance during demolding, and mitigating the shear stress damage to the microstructure during the demolding stage.
[0015] In the final product, the surface layer reduces the coefficient of friction, further improving the scratch and wear resistance of the light guide plate. At the same time, the polycarbonate segments have good compatibility with the bisphenol A type polycarbonate matrix, maintaining the optical transparency of the material system. In terms of optical structure, the elliptical dot array distributed on the surface of the light guide plate, combined with the amorphous or microcrystalline annular remelted protrusion microstructure at the edge, constitutes a composite optical control surface. When the light transmitted by total internal reflection inside the light guide plate encounters the composite microstructure, the outgoing light rays that would originally diverge in all directions are deflected towards the geometric normal direction and tend to converge under the refraction of the curved surface of the annular protrusion. This helps to improve the brightness of the positive field of view of the light guide plate.
[0016] Preferably, the fluorinated end-capped polycarbonate-siloxane block copolymer is formed by reactive polymerization of raw materials comprising the following components in parts by weight: 10 to 25 parts of bihydrogen-terminated polydimethylsiloxane; 1.8 to 4.5 parts of eugenol; 75 to 85 parts of bisphenol A; 78 to 86 parts of diphenyl carbonate; and 1 to 3 parts of 1H,1H,2H,2H-perfluoro-1-octanol.
[0017] To ensure that the proportions of each chain segment within the block copolymer meet the requirements of subsequent processing and optics, the specific polymerization reaction process is as follows:
[0018] Bis-terminated hydrogen-containing polydimethylsiloxane undergoes hydrosilylation with eugenol under the action of a catalyst. The allyl group in eugenol reacts with the hydrogen-silicon bonds at the ends of the polydimethylsiloxane to generate a polysiloxane precursor with phenolic hydroxyl groups at both ends. Subsequently, bisphenol A, diphenyl carbonate, and the polysiloxane precursor with phenolic hydroxyl groups at both ends undergo transesterification at high temperature and in the presence of a catalyst, releasing phenol, which then undergoes melt polycondensation to form a polycarbonate-siloxane block backbone. In the later stage of polycondensation, 1H,1H,2H,2H-perfluoro-1-octanol added to the system participates in the reaction. The aliphatic hydroxyl group of perfluorooctanol undergoes transesterification with the phenyl carbonate group at the end of the polymer macromolecule, grafting the perfluoroalkyl group onto the end of the molecular chain to complete the end capping. This structural design allows the polymer molecule to simultaneously possess fluorine, silicon, and carbonate groups, taking into account both matrix compatibility and surface migration activity.
[0019] Preferably, the total number of the elliptical dot array is 480,000 to 520,000, and the major axis length of the elliptical dots increases exponentially from the near-light end to the far-light end of the light guide plate, with a length range of 80 μm to 500 μm; the height of the annular remelted protrusion microstructure is 3 μm to 8 μm.
[0020] The exponentially increasing dot size distribution compensates for the attenuation of light energy as the transmission distance increases, thus making up for the light output at the far end and improving the illuminance uniformity of the overall light-emitting surface of the light guide plate. The protruding microstructure with a set size range takes into account both optical focusing ability and mold processing feasibility.
[0021] The method for preparing the high-brightness, high-wear-resistant, and high-strength automotive light guide plate includes the following steps:
[0022] After the components of the optical molding composition are mixed evenly, they are melt-extruded, granulated and dried to obtain optical molding composition particles;
[0023] The surface of the mold core is processed by laser ablation combined with high-pressure gas-assisted quenching and cooling, forming a mold core with microstructures of elliptical blind cavities and annular remelted protrusions at the edges.
[0024] The optical molding composition particles are added to an injection molding machine, and under dynamic mold temperature control and micro-vacuum degassing conditions, variable belt speed step injection filling is used.
[0025] After holding the pressure and cooling down, the mold is opened and the product is ejected to obtain the final product.
[0026] Due to the use of surface chilling processing and step injection molding, the replication rate of optical microstructures is improved. Laser ablation combined with quenching chilling process changes the crystallization state of the metal on the surface of the mold core, generating an amorphous or microcrystalline surface, improving the mechanical rigidity of the mold microstructure, and forming a micro-morphology with molding function on the cavity side. Variable belt speed step injection molding combined with micro-vacuum venting alleviates the flow resistance and gas trapping defects of polymer melt when filling small blind cavities, making the molding of micron-level optical structures more complete.
[0027] Preferably, the step of processing the mold core surface using a laser ablation combined with high-pressure gas-assisted quenching and cooling process to form a mold core with distributed elliptical blind cavities and edge annular remelted protrusions includes: on the surface of a pre-hardened martensitic stainless steel mold core substrate, a picosecond solid-state laser is used to ablate the dots row by row, while high-purity argon gas is continuously injected through a coaxial nozzle for high-pressure gas-assisted quenching and cooling, so that the splashed molten metal is rapidly solidified in situ at the edge of each elliptical dot; the laser output power of the picosecond solid-state laser is set to 15W to 25W, the pulse width to 10ps to 20ps, the repetition frequency to 80kHz to 120kHz, and the spot overlap rate to 60% to 75%; the injection pressure of the high-purity argon gas is set to 1.2MPa to 1.8MPa.
[0028] Ultrashort pulse lasers generate extremely high instantaneous peak power on the material surface, causing plasmaization and molten sputtering of the metal material. High-pressure cold high-purity argon gas, sprayed coaxially, isolates oxygen and avoids high-temperature oxidation of the metal surface. At the same time, it rapidly cools and quenches the molten metal droplets sputtered to the edge of the blind cavity. The extremely high cooling rate inhibits the growth process of metal grains and promotes the solidification of the melt to form amorphous or microcrystalline ring protrusions, increasing the strength of the regional microstructure.
[0029] Preferably, the steps of adding the optical molding composition particles into the injection molding machine and using variable belt speed step injection filling under dynamic mold temperature control and micro-vacuum venting conditions include: before mold closing, introducing superheated steam into the mold to preheat the mold core surface to 145°C to 155°C; in the middle and later stages of screw propulsion filling, simultaneously opening the micro-vacuum venting valve at the far end of the mold to reduce the absolute pressure in the mold cavity to -85kPa to -95kPa; and using a step-speed injection of the polymer melt into the mold cavity. Injection speed control: When the screw stroke is in the range of 0% to 55%, the first injection speed is set to 120mm / s to 150mm / s; when the screw stroke advances to the range of 55% to 95%, the second injection speed is set to 15mm / s to 25mm / s; the first injection speed is greater than the second injection speed; the steps of holding pressure, cooling and reducing temperature, and then opening the mold to eject the final product include: setting the holding pressure to 60MPa to 80MPa, and controlling the holding time to 4s to 6s.
[0030] The high mold temperature at the initial injection stage delays the surface solidification process of the polymer melt, maintaining a low melt viscosity. The first stage of the injection stroke corresponds to the small-sized dot area in the mold cavity, and a higher first injection speed can quickly fill the cavity, preventing the melt temperature from dropping excessively. The middle and later stages of the injection stroke correspond to the large-sized dot area, and a rapidly decreasing second injection speed combined with remote micro-vacuum evacuation accelerates the discharge of residual gas in the cavity, reducing the risk of scorching and flow marks caused by poor venting. The step-like speed switching matches the volume filling requirements of different sized dots, which not only improves the mold filling fidelity of the optical microstructure, but also helps to reduce the internal stress of the light guide plate after molding.
[0031] In summary, the present invention has at least one of the following beneficial technical effects:
[0032] 1. This invention uses fluorinated end-capped poly(carbonate-siloxane) block copolymer as a modifying component of the matrix material. During the injection molding stage, based on the low surface energy characteristics of the fluorinated and siloxane segments, a release slip layer is formed on the surface of the light guide plate. The release slip layer reduces the adhesion between the light guide plate and the mold cavity, reduces the frictional resistance during the demolding process, thereby reducing the shear stress damage to the surface microstructure during demolding. The surface layer after molding also reduces the friction coefficient of the final product and improves the scratch resistance and wear resistance of the light guide plate.
[0033] 2. The present invention distributes an elliptical dot array with amorphous or microcrystalline annular remelted protrusions on the surface of the light guide plate. When the light transmitted inside the light guide plate is emitted through the composite microstructure, it is deflected and focused in the geometric normal direction by the refraction of the annular protrusion curved surface, thereby improving the brightness of the positive field of view of the light guide plate. At the same time, the corresponding microcavity on the mold side is processed by laser ablation combined with high-purity argon quenching and cooling process, so that the in-situ solidified metal presents an amorphous or microcrystalline state. This processing method increases the structural stiffness of the microstructure in the corresponding area and delays the wear of the microstructure of the light guide plate under long-term vibration environment.
[0034] 3. This invention employs a molding process combining dynamic mold temperature control with variable belt speed step injection and micro-vacuum venting. A higher injection speed is used in the initial injection stage to maintain melt fluidity and quickly fill small dot areas. In the later stages of injection, the injection speed is reduced while simultaneously activating remote vacuum venting to accelerate the removal of gas from the cavity. The segmented mold filling speed switching matches the gradient increase in dot volume changes, alleviating localized gas trapping and flow marks when the melt fills tiny blind cavities, improving the fullness of the micron-level optical structure, and reducing internal residual stress after the light guide plate is formed. Attached Figure Description
[0035] Figure 1Figure 1 shows the surface phase and mechanical properties of the microstructure of the mold core of the present invention; wherein, Figure (a) is an X-ray diffraction pattern and Figure (b) is a nanoindentation load-displacement curve.
[0036] Figure 2 Figure (a) shows the depth distribution of XPS elements on the surface of the light guide plate of the present invention, and Figure (b) shows the depth distribution of F elements.
[0037] Figure 3 Figure 1 shows the transmission spectrum and gel permeation chromatography elution curve of the present invention; wherein, Figure (a) is the ultraviolet and visible light transmission spectrum curve, and Figure (b) is the gel permeation chromatography elution curve.
[0038] Figure 4 Figure 1 shows the secondary optical luminescence performance test diagram of the light guide plate of the present invention; wherein, Figure (a) is a curve of spatial luminescence angle and relative light intensity distribution of the light guide plate, and Figure (b) is a curve of brightness distribution of the light guide plate along the incident light side to the far end.
[0039] Figure 5 Figure (a) is a statistical chart of the continuous injection molding defect rate, and Figure (b) is a two-dimensional height profile curve of the mold core microstructure surface. Detailed Implementation
[0040] The following is in conjunction with the appendix Figure 1 - Appendix Figure 5 The present invention will be further described in detail below.
[0041] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0042] Bisphenol A type polycarbonate, CAS number 25037-45-0;
[0043] 2,2-Bis(4-hydroxyphenyl)propane, commonly known as bisphenol A, CAS number 80-05-7;
[0044] Diphenyl carbonate, CAS number 102-09-0;
[0045] Polymethylhydrosiloxane, commonly known as hydrogen-containing silicone oil, CAS number 63148-57-2;
[0046] 1H,1H,2H,2H-perfluoro-1-octanol, CAS number 647-42-7;
[0047] Tris(2,4-di-tert-butylphenyl) phosphite, commonly known as Antioxidant 168, CAS number 31570-04-4;
[0048] 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, commonly known as light stabilizer 234, CAS number 70321-86-7, with a purity greater than 99%.
[0049] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.
[0050] Preparation Example 1:
[0051] This preparation example provides a method for preparing a fluorinated end-capped poly(carbonate-siloxane) block copolymer, comprising the following steps:
[0052] Twenty parts of hydrogen-terminated polydimethylsiloxane and 3.6 parts of eugenol were added to a reaction vessel, and chloroplatinic acid at a concentration of 18 ppm was added. The reaction was carried out at 90 °C for 2.5 h to obtain a hydrosilylation reaction of the polysiloxane precursor.
[0053] In a jacketed reactor equipped with a mechanical stirrer, 80 parts of bisphenol A, 20 parts of dihydroxyl-terminated polysiloxane precursor, and 82 parts of diphenyl carbonate were added. Tetrabutyl titanate was added at a weight equivalent to 0.005% of the total weight of bisphenol A, dihydroxyl-terminated polysiloxane precursor, and diphenyl carbonate. Under the protection of high-purity nitrogen, the reaction system was heated to 155°C and kept at that temperature for 50 minutes to allow the materials to completely melt and undergo transesterification.
[0054] Two parts of 1H,1H,2H,2H-perfluoro-1-octanol were added to the reaction system. The temperature of the reactor was gradually increased to 270°C, and a vacuum was drawn in a stepwise manner at a rate of 10°C / min until the absolute pressure inside the reactor dropped to 80 Pa. The melt polycondensation reaction was carried out for 1.8 h. The phenol byproducts released from the reaction were collected through a condenser.
[0055] When the stirring torque of the reaction system reaches 35 N·m, high-purity nitrogen is introduced to break the vacuum, and strip-shaped melt is extruded from the bottom of the reactor. After cooling in a water tank, it is granulated to obtain fluorinated end-capped poly(carbonate-siloxane) block copolymer for later use. The fluorinated end-capped poly(carbonate-siloxane) block copolymer here is named fluorinated end-capped poly(carbonate-siloxane) block copolymer A.
[0056] Preparation Example 2:
[0057] This preparation example provides a method for preparing a fluorinated end-capped poly(carbonate-siloxane) block copolymer, comprising the following steps:
[0058] Ten parts of hydrogen-terminated polydimethylsiloxane and 1.8 parts of eugenol were added to a reaction vessel, and chloroplatinic acid at a concentration of 15 ppm was added. The reaction was carried out at 85°C for 2 hours to obtain a hydrosilylation reaction of the bi-hydroxyl-terminated polysiloxane precursor.
[0059] In a jacketed reactor equipped with a mechanical stirrer, 85 parts of bisphenol A, 10 parts of dihydroxyl-terminated polysiloxane precursor, and 86 parts of diphenyl carbonate were added. Tetrabutyl titanate was added at a weight equivalent to 0.003% of the total weight of bisphenol A, dihydroxyl-terminated polysiloxane precursor, and diphenyl carbonate. Under the protection of high-purity nitrogen, the reaction system was heated to 150°C and kept at that temperature for 45 minutes to allow the materials to completely melt and undergo transesterification.
[0060] Add 1 part of 1H,1H,2H,2H-perfluoro-1-octanol to the reaction system, gradually heat the reactor to 260℃, and simultaneously stepwise evacuate at a rate of 10℃ / min until the absolute pressure inside the reactor drops to 100Pa, and carry out the melt polycondensation reaction for 1.5h. The phenol byproducts released from the reaction are collected through a condenser.
[0061] When the stirring torque of the reaction system reaches 30 N·m, high-purity nitrogen is introduced to break the vacuum, and strip-shaped melt is extruded from the bottom of the reactor. After cooling in a water tank, it is granulated to obtain fluorinated end-capped poly(carbonate-siloxane) block copolymer for later use. The fluorinated end-capped poly(carbonate-siloxane) block copolymer here is named fluorinated end-capped poly(carbonate-siloxane) block copolymer B.
[0062] Preparation Example 3:
[0063] This preparation example provides a method for preparing a fluorinated end-capped poly(carbonate-siloxane) block copolymer, comprising the following steps:
[0064] 25 parts of hydrogen-terminated polydimethylsiloxane and 4.5 parts of eugenol were added to a reaction vessel, and chloroplatinic acid with a concentration of 20 ppm was added. The reaction was carried out at 95°C for 3 h to obtain a hydrosilylation reaction of the bi-hydroxyl-terminated polysiloxane precursor.
[0065] In a jacketed reactor equipped with a mechanical stirrer, 75 parts of bisphenol A, 25 parts of dihydroxyl-terminated polysiloxane precursor, and 78 parts of diphenyl carbonate were added. Tetrabutyl titanate was added at a weight equivalent to 0.008% of the total weight of bisphenol A, dihydroxyl-terminated polysiloxane precursor, and diphenyl carbonate. Under the protection of high-purity nitrogen, the reaction system was heated to 160°C and kept at that temperature for 60 minutes to allow the materials to completely melt and undergo transesterification.
[0066] Add 3 parts of 1H,1H,2H,2H-perfluoro-1-octanol to the reaction system, gradually raise the temperature of the reactor to 280℃, and simultaneously stepwise evacuate at a rate of 10℃ / min until the absolute pressure inside the reactor drops to 50Pa, and carry out the melt polycondensation reaction for 2 hours. The phenol byproducts released from the reaction are collected through a condenser.
[0067] When the stirring torque of the reaction system reaches 40 N·m, high-purity nitrogen is introduced to break the vacuum, and strip-shaped melt is extruded from the bottom of the reactor. After cooling in a water tank, it is granulated to obtain fluorinated end-capped poly(carbonate-siloxane) block copolymer for later use. The fluorinated end-capped poly(carbonate-siloxane) block copolymer here is named fluorinated end-capped poly(carbonate-siloxane) block copolymer C.
[0068] Example 1:
[0069] This embodiment provides a method for preparing a high-brightness, high-wear-resistant, and high-strength automotive light guide plate, including the following steps:
[0070] 80 parts by weight of bisphenol A type polycarbonate, 19.5 parts by weight of fluorinated end-capped poly(carbonate-siloxane) block copolymer A, 0.3 parts by weight of tris(2,4-di-tert-butylphenyl) phosphite, and 0.2 parts by weight of 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol were added to a high-speed mixer and mixed evenly. Then, the mixture was fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 250°C to 270°C. The granules were then dried at 120°C for 4 hours to obtain optically shaped composition particles.
[0071] Pre-hardened martensitic stainless steel was selected as the mold core matrix. An elliptical dot array of 500,000 dots was arranged on the curved surface of the mold core along the incident light side towards the far end. The major axis length of the dots increased exponentially from 80 μm at the near end to 400 μm at the far end. A picosecond solid-state laser with a wavelength of 1064 nm was used to ablate the dots row by row. The laser output power was set to 20 W, the pulse width to 15 ps, the repetition frequency to 100 kHz, and the spot overlap rate to 68%. During laser ablation, high-purity argon gas at a pressure of 1.5 MPa was continuously sprayed coaxially through a Laval nozzle for high-pressure gas-assisted quenching and cooling. This allowed the splashed molten metal to solidify in situ at the edge of each elliptical dot, forming an amorphous or microcrystalline annular remelted protrusion microstructure with a height of 5 μm.
[0072] The optical molding composition particles are added to an all-electric injection molding machine equipped with a micro-vacuum and dynamic mold temperature control system. The temperature gradient of the barrel from back to front is set to 260℃, 280℃, 295℃, and 290℃. Before the mold closes, superheated steam is introduced into the water channel on the back side of the mold cavity, causing the surface temperature of the mold core to rise sharply to 150℃. Then, the polymer melt is injected into the mold cavity. When the screw stroke is in the range of 0% to 55%, the small-size dot area is filled, and the injection speed is set to 135mm / s. When the screw stroke reaches 55% and advances to 95%, the large-size dot area is filled, and the injection speed is abruptly reduced to 20mm / s. At the same time, the micro-vacuum exhaust valve at the far end of the mold is opened to draw the absolute pressure in the mold cavity to -90kPa.
[0073] After the screw stroke reaches 95%, switch to the pressure holding mode. The pressure holding pressure is set to 70MPa and the pressure holding time lasts for 5 seconds. After the pressure holding is completed, cut off the high-temperature steam and introduce 18℃ cooling circulating water. When the overall temperature of the mold drops below 80℃, open the mold and eject it through the ejector pin system to obtain a high-brightness, high-wear-resistant, and high-strength automotive light guide plate.
[0074] Example 2:
[0075] This embodiment provides a method for preparing a high-brightness, high-wear-resistant, and high-strength automotive light guide plate, including the following steps:
[0076] 85 parts by weight of bisphenol A type polycarbonate, 14.5 parts by weight of fluorinated end-capped poly(carbonate-siloxane) block copolymer B, 0.2 parts by weight of tris(2,4-di-tert-butylphenyl) phosphite, and 0.3 parts by weight of 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol were added to a high-speed mixer and mixed evenly. Then, the mixture was fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 250°C to 270°C. The granules were then dried at 120°C for 4 hours to obtain optically shaped composition particles.
[0077] Pre-hardened martensitic stainless steel was selected as the mold core matrix. An elliptical dot array of 480,000 dots was arranged on the curved surface of the mold core along the incident light side towards the far end. The major axis length of the dots increased exponentially from 80 μm at the near end to 300 μm at the far end. A picosecond solid-state laser with a wavelength of 1064 nm was used to ablate the dots row by row. The laser output power was set to 15 W, the pulse width to 10 ps, the repetition frequency to 80 kHz, and the spot overlap rate to 60%. During laser ablation, high-purity argon gas at a pressure of 1.2 MPa was continuously sprayed coaxially through a Laval nozzle for high-pressure gas-assisted quenching and cooling. This allowed the splashed molten metal to solidify in situ at the edge of each elliptical dot, forming an amorphous or microcrystalline annular remelted protrusion microstructure with a height of 3 μm.
[0078] The optical molding composition particles are added to an all-electric injection molding machine equipped with a micro-vacuum and dynamic mold temperature control system. The temperature gradient of the barrel from back to front is set to 260℃, 280℃, 295℃, and 290℃. Before the mold closes, superheated steam is introduced into the water channel on the back side of the mold cavity, causing the surface temperature of the mold core to rise sharply to 145℃. Then, the polymer melt is injected into the mold cavity. When the screw stroke is in the range of 0% to 55%, the small-size dot area is filled, and the injection speed is set to 120mm / s. When the screw stroke reaches 55% and advances to 95%, the large-size dot area is filled, and the injection speed is abruptly reduced to 25mm / s. At the same time, the micro-vacuum exhaust valve at the far end of the mold is opened to draw the absolute pressure in the mold cavity to -85kPa.
[0079] After the screw stroke reaches 95%, switch to the pressure holding mode. The pressure holding pressure is set to 60MPa and the pressure holding time lasts for 4 seconds. After the pressure holding is completed, cut off the high-temperature steam and introduce 15℃ cooling circulating water. When the overall temperature of the mold drops below 80℃, open the mold and eject it through the ejector system to obtain a high-brightness, high-wear-resistant, and high-strength automotive light guide plate.
[0080] Example 3:
[0081] This embodiment provides a method for preparing a high-brightness, high-wear-resistant, and high-strength automotive light guide plate, including the following steps:
[0082] 75 parts by weight of bisphenol A type polycarbonate, 24.5 parts by weight of fluorinated end-capped poly(carbonate-siloxane) block copolymer C, 0.4 parts by weight of tris(2,4-di-tert-butylphenyl) phosphite, and 0.1 parts by weight of 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol were added to a high-speed mixer and mixed evenly. Then, the mixture was fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 250°C to 270°C. The granules were then dried at 120°C for 4 hours to obtain optically shaped composition particles.
[0083] Pre-hardened martensitic stainless steel was selected as the mold core matrix. An elliptical array of 520,000 dots was arranged on the curved surface of the mold core along the incident light side towards the far end. The major axis length of the dots increased exponentially from 100 μm at the near end to 500 μm at the far end. A picosecond solid-state laser with a wavelength of 1064 nm was used to ablate the dots row by row. The laser output power was set to 25 W, the pulse width to 20 ps, the repetition frequency to 120 kHz, and the spot overlap rate to 75%. During laser ablation, high-purity argon gas at a pressure of 1.8 MPa was continuously sprayed coaxially through a Laval nozzle for high-pressure gas-assisted quenching and cooling. This allowed the splashed molten metal to solidify in situ at the edge of each elliptical dot, forming an amorphous or microcrystalline annular remelted protrusion microstructure with a height of 8 μm.
[0084] The optical molding composition particles are added to an all-electric injection molding machine equipped with a micro-vacuum and dynamic mold temperature control system. The temperature gradient of the barrel from back to front is set to 260℃, 280℃, 295℃, and 290℃. Before the mold closes, superheated steam is introduced into the water channel on the back side of the mold cavity, causing the surface temperature of the mold core to rise sharply to 155℃. Then, the polymer melt is injected into the mold cavity. When the screw stroke is in the range of 0% to 55%, the small-size dot area is filled, and the injection speed is set to 150mm / s. When the screw stroke reaches 55% and advances to 95%, the large-size dot area is filled, and the injection speed is abruptly reduced to 15mm / s. At the same time, the micro-vacuum exhaust valve at the far end of the mold is opened to draw the absolute pressure in the mold cavity to -95kPa.
[0085] After the screw stroke reaches 95%, switch to pressure holding mode, set the pressure to 80MPa, and hold for 6 seconds. After pressure holding, cut off the high-temperature steam and introduce 20°C cooling circulating water. When the overall mold temperature drops below 80°C, open the mold and eject the high-brightness, high-wear-resistant, and high-strength automotive light guide plate through the ejector pin system.
[0086] Comparative Example 1:
[0087] Compared with Example 1, the difference is that instead of using laser and high-pressure gas-assisted quenching and cooling process, the mold core dots are processed by traditional precision CNC machine tool impact process. The dots formed on the surface of the mold core are flat-bottomed blind cavities with no annular remelted protrusion microstructures at the edges. All other aspects are the same.
[0088] Comparative Example 2:
[0089] The difference from Example 1 is that when using a picosecond solid-state laser for dot ablation, the high-pressure continuous injection of high-purity argon gas is turned off; otherwise, they are the same.
[0090] Comparative Example 3:
[0091] Compared with Example 1, the difference is that the dynamic mold temperature control system and the micro-vacuum exhaust valve are turned off, superheated steam is not introduced for preheating before mold closing, and the polymer melt is injected into the mold cavity at a constant injection speed of 135mm / s throughout the process. All other aspects are the same.
[0092] Comparative Example 4:
[0093] Compared with Example 1, the difference is that, when preparing the optically shaped composition particles, fluorine-containing end-capped poly(carbonate-siloxane) block copolymer A is not added, but the amount of bisphenol A type polycarbonate is increased to 99.5 parts by weight, while the rest are the same.
[0094] Comparative Example 5:
[0095] Compared with Example 1, the difference is that the dot layout on the mold core surface is replaced with a uniform array without size gradient, the major axis length of the dots is 60μm, and the total number is increased to 1.5 million, while the rest are the same.
[0096] Test Example 1:
[0097] This test example measures the metallurgical phase and mechanical hardness of the remelted layer of the mold core. The test objects include the curved mold core prepared in Example 1, the mold core prepared in Comparative Example 2, and the untreated pre-hardened martensitic stainless steel matrix.
[0098] Grazing incidence scanning tests were performed on the surface region of each test sample using an X-ray diffractometer. The radiation source was set to CuKα, the wavelength to be 0.154 nm, the tube voltage to be 40 kV, and the tube current to be 40 mA. The grazing incidence angle was fixed at 1° to limit the penetration depth of the X-rays, so that the collected diffraction signals mainly originated from the surface region of the microstructure. The scanning range 2θ was set to 30° to 90°, and the scanning rate was set to 2° / min. Full-spectrum diffraction data were acquired and recorded.
[0099] The hardness and elastic modulus of the microstructure protrusions of each test sample were tested using a nanoindenter. A Berkovich diamond indenter was used, with the maximum load set to 10 mN and the loading and unloading rates both set to 0.5 mN / s. After reaching the maximum load, the holding time was set to 10 s to eliminate the interference of material creep on the unloading curve. Fifteen different locations were randomly selected in the microstructure region of each sample for indentation testing. The two extreme values with the largest deviations were removed, and the arithmetic mean was calculated. Continuous load and displacement curves were recorded.
[0100] Table 1. Test results of the surface nanoindentation mechanical properties of each mold core microstructure:
[0101] sample Nanohardness (GPa) Elastic modulus (GPa) Maximum indentation depth (nm) Untreated substrate 5.23 204.16 213.81 Comparative Example 2 6.47 212.83 191.05 Example 1 9.68 248.15 138.42
[0102] According to Table 1 and Figure 1 The nanohardness of Example 1 was measured to be 9.68 GPa, and the elastic modulus was 248.15 GPa, both showing an increase compared to the untreated matrix and Comparative Example 2. Meanwhile, the load-displacement curves showed that the maximum indentation depth of Example 1 decreased under the same load conditions. This reflects that the laser remelting process combined with high-pressure inert gas forced convection heat transfer creates a cooling gradient on the metal surface, affecting grain development during the solidification process. This promotes the transformation of some remelted layer structures into amorphous or microcrystalline phases. The formation of microcrystalline structures restricts dislocation slip within the material. The hardness increase resulting from the change in microcrystalline structure is of reference value for resisting microcrystalline deformation under periodic high-pressure injection molding conditions.
[0103] Test Example 2:
[0104] The light guide plates prepared in Example 1 and Comparative Example 4 were selected as test objects. Elemental depth analysis of the light guide plate surface was performed using X-ray photoelectron spectroscopy. AlKα was used as the X-ray emission source, and the vacuum level of the test chamber was maintained below 1 × 10⁻⁶. -8Under mbar conditions, the sample surface was sputtered and peeled layer by layer using an argon ion gun. The sputtering energy was set to 2kV, and the etching rate was calibrated to 1nm / min with Ta2O5 as the reference standard. Continuous etching and scanning were performed at 2nm depth intervals. The photoelectron spectral signals of F1s and Si2p orbitals within a total depth range of 100nm were collected. After correction by the instrument's built-in sensitivity factor, the atomic percentage content of the elements at each depth position was calculated, and the test data along the depth distribution was recorded.
[0105] Light guide plates prepared in Examples 1, 2, 3, and Comparative Example 4 were selected as test objects. Surface wettability tests were conducted at room temperature (25°C) using a contact angle meter. Deionized water and diiodomethane were used as test probe liquids, respectively. The volume of a single droplet was controlled to be 2 μL using a micro-injection pump. The droplets were transferred to the test surface of each light guide plate using the pendant drop method. After the droplet morphology stabilized, the contact angle values were recorded. Five non-overlapping measurement points were randomly selected on the surface of each sample for testing and the arithmetic mean was calculated. The corresponding surface free energy values were calculated using the OWRK model combined with the surface tension component data of the droplets.
[0106] Table 2. Contact angle and surface free energy data for each test object:
[0107] sample Deionized water contact angle (°) Diiodomethane contact angle (°) Surface free energy (mN / m) Example 1 108.43 76.12 21.63 Example 2 105.78 73.59 23.27 Example 3 111.91 79.24 19.41 Comparative Example 4 82.65 45.41 41.58
[0108] According to Table 2 and Figure 2 It can be seen that in Example 1, a high concentration of F and Si elements was detected in the near-surface region, and the atomic percentage gradually decreased with the increase of the test depth. In Comparative Example 4, the content of F and Si elements in each depth range was close to the baseline level. This data distribution reflects that the fluorinated end-capped poly(carbonate-siloxane) block copolymer added to the system was enriched and assembled on the outer surface of the polymer melt under the action of injection molding and thermodynamics. Combined with the surface wettability test data, the surface migration of fluorinated silicon segments caused the corresponding material to increase the water contact angle and decrease the surface free energy value, resulting in a low surface energy state at the light guide plate interface. The change of the physicochemical interface weakened the interaction force between the polymer matrix and the rigid metal micro / nano surface. The establishment of this property has a synergistic effect on reducing the demolding resistance after molding and reducing the micro-adhesion and pulling phenomenon.
[0109] Test Example 3:
[0110] The optical molding composition particles before injection molding in Example 1, as well as the vehicle-mounted light guide plates prepared in Examples 1, 2, 3, and Comparative Example 3, were selected as test objects. A sheet sample with a size of 20mm×20mm was cut from the dense microstructure area at the far end of each light guide plate sample. The transmittance of the cut sample was scanned using an ultraviolet and visible spectrophotometer. The scanning wavelength range was set to 380nm to 780nm, and the data acquisition interval was set to 1nm. The full spectrum transmittance curve of the visible light band was obtained, and the yellowness index of the corresponding area was calculated in combination with the ASTM E313 standard.
[0111] Approximately 8 mg of material was weighed from both the cut sample and the optical composition particles before injection molding. Each sample was immersed in 15 mL of chromatographic-grade tetrahydrofuran solvent and allowed to stand at room temperature for 24 hours in a sealed container until completely dissolved. The solution was then filtered through a 0.22 μm pore size polytetrafluoroethylene (PTFE) membrane. The molecular weight of the filtrate was determined using a gel permeation chromatography system equipped with a differential refractive index detector. The detection environment was set at a column temperature of 35 °C, a mobile phase of tetrahydrofuran, a flow rate of 1.0 mL / min, and a single injection volume of 50 μL. The elution time and refractive index intensity curve of the effluent were recorded. The weight-average molecular weight of the test sample was calculated using a pre-calibrated narrow-distribution polystyrene standard curve. The molecular weight retention rate of each light guide plate sample relative to the particles before molding was also calculated.
[0112] Table 3. Yellowness index and molecular weight test data for each test subject:
[0113] sample Yellowness Index (YI) Weight-average molecular weight (10⁴ g / mol) Molecular weight retention rate (%) Example 1: Particles before molding 1.18 4.86 - Example 1 1.42 4.79 98.56 Example 2 1.57 4.75 97.74 Example 3 1.36 4.81 98.97 Comparative Example 3 6.25 3.52 72.43
[0114] According to Table 3 and Figure 3 The test results showed that, in the transmission spectrum, Examples 1, 2, and 3 maintained relatively stable high transmittance throughout the visible light band, with the corresponding yellowness index remaining in the low range of 1.3 to 1.6. Comparative Example 3 showed attenuation absorption in the short-wavelength band of 400 nm to 500 nm, resulting in a downward shift in the overall transmittance curve and a higher measured yellowness index. In addition, the gel permeation chromatography elution curves showed that the elution peak position of Example 1 was close to the main peak position of the particles before molding, with a molecular weight retention rate of over 98%. The main elution peak of Comparative Example 3 shifted towards the longer elution time direction, and the peak width increased, resulting in a numerical decrease in the calculated weight-average molecular weight and molecular weight retention rate.
[0115] The comparison shows that when using a large-size micro-nano blind cavity array mold for molding, conventional constant high-speed filling without venting causes the trapped air inside the microcavity to be compressed rapidly. This leads to thermo-oxidative degradation and chain breakage of polymer segments in the adiabatic heating environment, resulting in yellowing of the material and a reduction in molecular weight. By introducing variable temperature control to maintain melt fluidity, and combining step injection deceleration with micro-vacuum venting, the hydrodynamic state of the polymer melt wavefront is changed. This provides a time and space channel for the overflow of residual gas in the blind cavity, prevents the occurrence of local high-temperature adiabatic compression, and maintains the stability of the chemical structure and optical properties of the polycarbonate matrix during the microstructure filling process.
[0116] Test Example 4:
[0117] Vehicle-mounted light guide plates prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 5 were selected as test objects. Each light guide plate was assembled into a standard backlight test fixture equipped with a single-sided LED light source. The light source was kept lit at a constant current in a dark room at 25°C and stabilized for 30 minutes. A spectral photometer was used to perform spatial light distribution tests on the light-emitting surface of the light guide plate. The test probe was rotated around the center of the light-emitting surface of the sample, and the scanning angle range was set to -90° to +90°. The data on the change of relative light intensity with the light-emitting angle were recorded, and the axial center brightness value in the 0° normal direction was extracted.
[0118] Keeping the light source fixture and light emission state unchanged, divide the effective light emission area of the light guide plate into grids at equal intervals, select 9 standard test points covering the near light end, central area and far light end, and use a color luminance meter to measure the absolute luminance value of these 9 points in the direction perpendicular to the light emission surface. Record the minimum and maximum luminance values in the test data, and calculate the percentage of the minimum and maximum values as the overall light emission uniformity of the light guide plate.
[0119] Table 4. Test data of optical luminescence performance of light guide plates for each test object:
[0120] sample Axial center brightness (cd / m²) Minimum brightness at nine points (cd / m²) Maximum brightness at nine points (cd / m²) Luminescence uniformity (%) Example 1 4583.6 4125.8 4774.2 86.41 Example 2 4417.2 3968.1 4652.7 85.28 Example 3 4721.5 4256.4 4879.6 87.22 Comparative Example 1 3128.9 2685.2 3218.5 83.43 Comparative Example 5 3854.3 1856.7 6472.1 28.68
[0121] According to Table 4 and Figure 4 It can be seen that in the spatial emission angle and relative light intensity distribution test, the emission energy of Example 1 is concentrated towards the 0° normal direction, and the measured axial center brightness value is higher than that of Comparative Example 1; the relative light intensity distribution of Comparative Example 1 shows a broadened divergence characteristic, and the beam overflows in the large angle region deviating from the normal. At the same time, the brightness distribution and uniformity test data along the path show that the brightness fluctuation of Example 1 is small throughout the entire test span from the near light end to the far light end, and the light emission uniformity is at a high level; the brightness curve of Comparative Example 5 shows an extreme value on the near light side, and then decays with the increase of distance, and the overall emission uniformity drops to 28.68%;
[0122] The distribution characteristics of optical performance reflect that the micro-annular remelting protrusions formed by the core replication transfer change the geometric morphology of the blind cavity edge, constructing a micro-collimation structure on the surface of the light guide plate medium. When the outgoing light passes through the annular protrusion interface, it undergoes secondary refraction and edge total internal reflection, causing the diverging beam to be deflected and converged in the normal direction, overcoming the scattering problem caused by traditional flat-bottomed microcavities. Combined with the morphological layout where the length of the dot matrix increases exponentially from the near-light end to the far-light end, it compensates for the light energy attenuation during the total internal reflection propagation process, and coordinates the directional utilization rate of the light energy of the light guide plate with the uniformity of surface emission.
[0123] Test Example 5:
[0124] The optical molding composition particles and corresponding processing molds of Examples 1, 2, 3, Comparative Example 2 and Comparative Example 4 were selected as test objects. The simulated industrial mass production test was carried out continuously for 100,000 cycles on an all-electric injection molding machine according to the preparation parameters. During the continuous production process, the sampling period was 10,000 cycles. The number of defective products caused by demolding damage such as microstructure adhesion and pull-out, surface whitening and micro-nano fracture was counted. The overall demolding defect rate of each sample was calculated and recorded.
[0125] After 100,000 injection molding cycles, each mold was disassembled and its surface was cleaned and degreased. A step-type surface profilometer was used to perform a two-dimensional height scan of the microstructure-dense area at the distal end of the mold core. The probe scanning length was set to 200 μm, the scanning rate to 0.1 mm / s, and the contact force to 1 mg. The two-dimensional height coordinate curve of the micromorphology was recorded, and the average peak height of the remelted protruding microstructure in the test area was extracted. The measured values were compared with the initial mold scanning height before injection molding wear, and the height retention rate of the microstructure of each mold core was calculated.
[0126] Table 5. Stability evaluation data for each test object in continuous mass production of 100,000 cycles:
[0127] sample Demolding defect rate (%) Initial protrusion height (μm) Height (μm) after 100,000 cycles High retention rate (%) Example 1 1.26 5.06 4.91 97.04 Example 2 1.78 3.04 2.89 95.07 Example 3 0.95 8.12 7.95 97.91 Comparative Example 2 18.64 4.98 3.12 62.65 Comparative Example 4 43.52 5.03 4.75 94.43
[0128] According to Table 5 and Figure 5 The test results show that in Example 1, during the simulated production of 100,000 consecutive molding cycles, the demolding defect rate remained at a low level, and the height retention rate of the mold microstructure reached 97.04%. In Comparative Example 4, the demolding defect rate showed a trend of gradually increasing with the increase of injection molding cycles, and the overall defect rate was relatively high. After 100,000 molding cycles, the micro-remelted protrusions on the mold surface of Comparative Example 2 underwent compression deformation, and the two-dimensional height profile curve showed a decrease in peak height, with the height retention rate decreasing to 62.65%. This set of long-term operation test comparisons reflects that the lack of low surface energy materials in the molding composition system will lead to an increase in interfacial adhesion, causing the light guide plate microstructure to bear a large shear tensile stress at the moment of demolding, increasing the probability of surface whitening or micro-fracture.
[0129] Meanwhile, if the mold surface is not subjected to high-pressure gas-assisted quenching and cooling process, the metal matrix with conventional hardness and phase will undergo plastic collapse under the high pressure of periodic polymer melt injection and thermodynamic alternating load. Through the establishment of the interface slip characteristics of the molding material and the synergistic cooperation of the phase transformation hardening microstructure on the mold surface, the frictional resistance between the polymer and the rigid metal interface is reduced, and the mold's ability to resist periodic compressive stress deformation is maintained, providing material and process adaptability support for long-term continuous demolding of microstructured optical components.
[0130] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-brightness, high-wear-resistant, and high-strength automotive light guide plate, characterized in that, The light guide plate is made of an optical molding composition comprising the following components in parts by weight: Bisphenol A type polycarbonate: 75 to 85 parts; Fluorinated end-capped poly(carbonate-siloxane) block copolymers that enrich the surface during injection molding to reduce surface free energy and form a release slip layer: 14.5 to 24.5 parts; Tris(2,4-di-tert-butylphenyl) phosphite: 0.2 to 0.4 parts; 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol: 0.1 to 0.3 parts; The light guide plate has an elliptical dot array formed by a composite transfer distributed on the light incident side distal surface. The edges of the elliptical dots have amorphous or microcrystalline annular remelted protrusion microstructures to deflect and converge the diverging outgoing light beam toward the normal direction.
2. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 1, characterized in that, The fluorinated end-capped poly(carbonate-siloxane) block copolymer is synthesized by reaction polymerization of raw materials comprising the following components in parts by weight: Double-ended hydrogen-containing polydimethylsiloxane: 10 to 25 parts; Eugenol: 1.8 to 4.5 parts; Bisphenol A: 75 to 85 parts; Diphenyl carbonate: 78 to 86 parts; 1H,1H,2H,2H-perfluoro-1-octanol: 1 to 3 parts.
3. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 1, characterized in that, The total number of the elliptical dot array is between 480,000 and 520,000. The major axis length of the elliptical dots increases exponentially from the near-light end to the far-light end of the light guide plate, with a length range of 80μm to 500μm.
4. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 1, characterized in that, The height of the annular remelting protrusion microstructure is 3 μm to 8 μm.
5. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 1, characterized in that, The preparation method of the high-brightness, high-wear-resistant, and high-strength automotive light guide plate includes the following steps: After the components of the optical molding composition are mixed evenly, they are melt-extruded, granulated and dried to obtain optical molding composition particles. The surface of the mold core is processed by laser ablation combined with high-pressure gas-assisted quenching and cooling, forming a mold core with microstructures of elliptical blind cavities and annular remelted protrusions at the edges. The optical molding composition particles are added to an injection molding machine, and under dynamic mold temperature control and micro-vacuum degassing conditions, variable belt speed step injection filling is used. After holding the pressure and cooling down, the mold is opened and the product is ejected to obtain the final product.
6. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 5, characterized in that, The step of processing the mold core surface using a laser ablation combined with high-pressure gas-assisted quenching and cooling process to form a mold core with microstructures distributed with elliptical blind cavities and annular remelted protrusions on the edges includes: On the surface of the pre-hardened martensitic stainless steel mold core, a picosecond solid-state laser is used to ablate the dots line by line. At the same time, high-purity argon gas is continuously injected through a coaxial nozzle for high-pressure gas-assisted quenching and cooling, so that the splashed molten metal solidifies rapidly in situ at the edge of each elliptical dot.
7. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 5, characterized in that, The steps of adding the optical molding composition particles into an injection molding machine and filling the mold using a variable belt speed step injection method under dynamic mold temperature control and micro-vacuum degassing conditions include: Before closing the mold, hot water steam is introduced into the mold to preheat the surface of the mold core to 145°C to 155°C; in the middle and later stages of the screw pushing and filling the mold, the micro-vacuum exhaust valve at the far end of the mold is opened simultaneously to draw the absolute pressure in the mold cavity to -85kPa to -95kPa.
8. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 5, characterized in that, The steps of adding the optical molding composition particles into an injection molding machine and filling the mold using a variable belt speed step injection method under dynamic mold temperature control and micro-vacuum degassing conditions include: The injection speed of the polymer melt into the mold cavity is controlled by a step-down mechanism: when the screw stroke is in the range of 0% to 55%, the first injection speed is set; when the screw stroke advances to the range of 55% to 95%, the second injection speed is set; the first injection speed is greater than the second injection speed.
9. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 8, characterized in that, The first injection speed is 120 mm / s to 150 mm / s, and the second injection speed is 15 mm / s to 25 mm / s; The steps of holding pressure, cooling down, opening the mold, and ejecting the product to obtain the final product include: The holding pressure is set to 60MPa to 80MPa, and the holding time is controlled to 4s to 6s.
10. The high-brightness, high-wear-resistant, and high-strength automotive light guide plate according to claim 5, characterized in that, The step of using a picosecond solid-state laser to ablate the dots line by line on the surface of a pre-hardened martensitic stainless steel mold core, while simultaneously continuously injecting high-purity argon gas through a coaxial nozzle for high-pressure gas-assisted quenching and cooling, so that the splashed molten metal solidifies rapidly in situ at the edge of each elliptical dot, includes: The picosecond solid-state laser output power is set to 15W to 25W, the pulse width to 10ps to 20ps, the repetition frequency to 80kHz to 120kHz, and the spot overlap rate to 60% to 75%. The injection pressure of high-purity argon gas is set to 1.2 MPa to 1.8 MPa.